Handling Of Ilium, Os Femur Fractures And Sacroiliac Luxation In Cat - Olga Olga; Muhammad Hambal; Syafruddin Syafruddin (Jurnal Medika Veterinaria, 2022)
Bone fracture is a crack or break in the bone which results in loss of continuity in the bone. In this study, a persian male cat, weight 3.9 kg, aged 3 years old was unable to stand up and move both extremities caudalis (posterior). Anamnesis showed that the cat was hit by a car. The results of radiographic examination in the ventrodorsal position showed a fracture of the body of the illium, fracture of the femur and sacroiliac luxation. The action taken was open reduction internal fixation (ORIF) which was fixed with a bone plate recon 2.0 veterinary cuttable plate (VCP) 5 holes and a 2.0 mm:12 mm cortical self-tapping screw on fractured of the body of ilium bone, bone plate 2.0 veterinary cuttable plate (VCP) with 4 holes and 2.0 mm:14 mm cortical self-tapping screws on fractured femur bone, and fixation with 2.5 mm:16 mm cortical non-self-tapping screws on bones that had sacroiliac luxation. On the 3rd day after surgery, the patient's hind legs began to move, and one week after surgery, the patient was able to stand and walk slowly.